Advanced Applications of Fuel Cells during the COVID-19 Pandemic. (11th June 2021) - Afroze, Shammya; Reza, Md Sumon; Cheok, Quentin; Islam, Shafi Noor; Abdalla, Abdalla M.; Taweekun, Juntakan; Azad, Abul K.; Khalilpoor, Nima; Issakhov, Alibek
Abstract : COVID-19 was identified all over the world as a pandemic in December 2019. This novel coronavirus affects the lower respiratory area, which causes pneumonia in the human body and transfers from human to human. Every day, the number of new patients and the number of deaths are increasing immensely, while specific drugs for this virus are still being developed. Hospitals are struggling to accommodate patients, resulting in a large number of temporary hospitals. These makeshift hospitals need an uninterrupted power supply to continuously maintain all the electrical facilities. Fuel cells, especially solid oxide fuel cells, play an essential role in meeting the additional energy needs of humankind during this critical moment. SOFCs are able to supply power to those makeshift hospitals from the main hospital building, as well as supplying electricity to locked-down residential areas to ease the strain on the electrical grid during this pandemic situation. As a result of their extensive applicability and numerous uses, SOFCs can be used to address electrical needs challenges in various sectors.